Leaders or jugglers? the principal dilemma : Irish second-level principals' narratives, identifying selected factors that encourage/limit their acting ethically - Chughtai, Naila Burney (Trinity College (Dublin, Ireland). School of Education, 2012)
School principals play a significant role in the effective running of schools. They are confronted by countless demands, expectations and challenges while trying to maintain balance in their decision-making about contradictory, yet complementary, considerations, such as the emphases to place on pedagogy/education, democracy/authority and pastoral care/academic teaching. The main purpose of this study was to examine these dualisms on the part of Irish second-level principals. Specifically, the research looks at their background influences and the impact of these on their current practices especially in the ways they communicate and interact, both with people in their schools and external agencies linked to the schools.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin.